Extraction of pectin from cocoa shell and its characterization by FT-IR analysis - Aparicio Huablocho, Jordan Alexis (2024)
Peru is among the main cocoa exporters, achieving a notable increase in production and, along with it, a growing generation of waste. These wastes, when destined for landfills, lead to pollution that significantly disturbs the environment. The cob is the main waste and is rescued for its pectin content. In this context, the main objective of this research is to explore the viability of extracting pectin from the cocoa shell (Theobroma cacao L.), coming from waste. of the cocoa industry of Peca-Amazonas. To achieve this purpose, a hydrolysis process was implemented at 70 ºC for 120 minutes, using a 0.1 N solution of hydrochloric, fumaric and citric acid as extraction agents. The samples obtained were detailed characterized in terms of yield, equivalent weight, methoxyl degree and AAG content. Likewise, they were characterized using the FT-IR technique, allowing the degree of esterification (DE) to be determined in each case. The results presented pectins with a low degree of esterification (6.11 - 43.14 %), through deconvolution and validated with the potentiometric titration method. This finding establishes a promising outlook for future scientific applications and developments.